Pemberdayaan dan Perencanaan Kawasan - Fery Murtiningrum (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Murtiningrum F. 2020. Empowerment and Planning Of Agricultural Area. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Community empowerment is very often discussed in almost all agricultural development activities, but it is a question mark whether community empowerment is really carried out in the process of planning agricultural areas in the context of agricultural development. There is very little data that shows that community empowerment is carried out in the agricultural area planning process. For this reason, this study aims to examine concepts related to empowerment and agricultural area planning.This research is based on a review of the philosophy or concept of empowerment, regional planning in research journals, literature books, national reports, regional and international organizations, thesis, seminar proceedings and others. The main theories used are the concept of empowerment, planning, development, and the area. Based on the results of the analysis of the study, it shows that empowerment plays an important role in the area planning process, so that the planning that has been compiled by the Government is to achieve its goals and can be carried out according to the expected objectives. The active role of the community is important to be involved in every stage of area planning so that at the time of the implementation of the planning results it can be carried out properly and on target.